Pendampingan Ekonomi Kreatif UMKM Keripik Kentang Mustofa di Kelurahan Air Dingin Kota Pekanbaru - Fany, Kinanti Resti; Hermita, Neni; Pasaribu, Danu Mangippu; Mulya, Gita Permata; Hafizalfiqri, Muhammad; Sanda, Nabila; Ananda, Rikki; Yulia, Rischa; Syafira; Fajar, Taufiq Afif; Andini, Tri (Journal of Community Engagement Research for Sustainability, 2024)
Indonesia has an excellent opportunity to increase national economic growth by developing a creative economy. As one of the new alternatives to drive the national economy, the creative economy sector supports the creation of added value to domestic products and the developing creative services that can support Indonesia's economic growth. The use of online media is the right choice for entrepreneurs to develop the business they run. The public already knows many MSMEs, however, only among the owners and known by word of mouth. Data collection methods used are observation, interviews, and documentation. Researchers used objects for this research from the owners of SMEs themselves. Various ways of coaching MSME owners by implementing several strategies: digitally marketing products, creating packaging logos for MSMEs, and finally registering a business in OSS and creating a Business Identification Number.